Pollution, profits, and stakeholders: The constraining effect of economic performance on CEO concern with stakeholder expectations - Dooley, Robert S.; Lerner, Linda D. (1994)
This study examined the constraining effect of economic performance on the relationship between CEO stakeholder orientations and four pollution performance categories. Economic performance was found to moderate the relationship for two of the four categories. Additionally economic performance was found to consistently interact with some CEO stakeholder orientations and not others. Overall the results suggest that CEO concern with stakeholder expectations is in large part moderate by the economic performance of the firm.
Keywords: Stakeholder Expectation; Stakeholder Orientation; Performance Category; Economic Performance; Economic Growth